Probable Pulmonary Blastomycosis in a Wild Coyote (Canis latrans) - Luis E. Rodríguez-Tovar; Alicia M. Nevárez-Garza; Ricardo Vladimir Barajas-Juárez; Juan J. Zarate-Ramos; Rogelio A. Ledezma-Torres; Armando Trejo-Chávez (Case Reports in Veterinary Medicine)
A female coyote (Canis latrans) was fatally injured by a vehicle on a road in San Luis Potosi, Mexico. Because of deteriorating clinical signs, the animal was euthanized. Postmortem examination of the lungs showed numerous small multifocal white nodules (0.5–1 cm diameter) disseminated throughout. Histopathologic examination revealed multifocal coalescing granulomas with abundant macrophages, numerous neutrophils, fibroblasts, plasma cells, and lymphocytes. Abundant intracellular and extracellular thick-walled, refractile, spherical yeasts (10–15 μm) were observed within the granulomas. The yeasts were intensely PAS-positive, with granular protoplasm. Broad-based single budding yeasts were occasionally present. Based on the microscopic findings of the pulmonary lesions and the morphological features of the organism, a diagnosis of chronic pyogranulomatous pneumonia caused by Blastomyces dermatitidis was made. To our knowledge, the case described herein is the first report of pulmonary blastomycosis in a wild coyote.